Artificial intelligence in K-12 instruction: the role of teacher professional development - Mah, Dana-Kristin; Groß, Nele; Egloffstein, Marc; Prilop, Christopher Neil (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This study examines 532 school teachers’ perspectives on instructional quality, new teaching and learning opportunities, and the necessity for professional development (PD) activities related to artificial intelligence (AI) for K-12 education. Quantitative analyses revealed that AI-related PD opportunities are utilized to a limited extent thus far. However, the frequency of participation and satisfaction with the training are significantly and positively associated with key aspects of instructional quality (cognitive activation, classroom management, individualization, supportive climate). Furthermore, qualitative analyses indicate that the teaching profession is in its early stages of AI integration. The findings suggest that the transformative potential of AI for instruction remains either unclear to practitioners or beyond their current capacity for implementation. These results emphasize the importance of PD in AI for teaching in K-12 schools in the age of AI.
Keywords: Artificial Intelligence; Teachers; Germany; Denmark; Instructional Quality; Professional Development